THE INFLUENCE OF DIGITAL PAYMENT AND SALES PROMOTION TOWARDS CUSTOMER PURCHASE INTENTION AT CONVENIENCE STORES (CASE STUDY OF ALFAMART AND ALFAMIDI IN CITRALAND, MANADO) - Tan, Timoty C. A.; Pangemanan, Sifrid. S.; Saerang, Regina T. (Universitas Sam Ratulangi, 2021)
The digitalization has become the new era that penetrate so many lives area including business. With the advantages offered by the digitalization, businesses like retail industry adopted the technology to facilitate their shopping and transaction related activities. From availability of digital payment to sales promotion, it is all used to influence the customer purchase intention. Alfamart and Alfamidi are the main role in Manadoâ€™s retail industry with the highest number of stores. With the changes in consumer lifestyle, consumer also shift into modern markets as they can fulfill the consumers daily necessities complete with advanced facilities. The objective of this study is to find out the factors affecting the customer purchase intention using four dependent variables which are Digital Payment, Sales Promotion, Perceived Ease of Use, Perceived Usefulness, and an independent variable that is Purchase Intention. This study uses a quantitative method and multiple linear regression to analyze the influence of the dependent variables toward the independent variable. This study shows that Digital Payment, Perceived Ease of Use and Perceived Usefulness has no significant effect to the customer purchase intention while Sales Promotion has a significant effect to the customer purchase intention. From the result, there are recommendations offered such as increasing the availability of digital payment and raise the product awareness, simplify, and enhance the technology and to maintain and be creative with the sales promotion.Â Keywords: digital payment, financial technology, convenience store.